Standardization of a test to evaluate the ability to read and diagnose its difficulties for a child of 7 to 10 years in the Arabic-Algerian linguistic environment. - Yassine, Ladjal (Technium Social Sciences Journal, 2022)
The article deals with the psychometric procedural steps for constructing and standardizing a test to assess the reading abilities of the schooled child in the primary stage and diagnose reading disability (dyslexia). The test was standardized on a total sample of 280 male and female students between the ages of 7 to 10 years. based on the dual reading model of Coltheart [1], [2] and the L'Alouette text test by researcher Lefevrais [3], [4].The experimental method was adopted to ascertain the psychometric stages represented mainly in the validity and reliability of the scale items. Which includes the reading text «City Garden in this study on 243 unfamiliar words for the child and outside the curriculum. in addition to lists of reading words. non-words and pseudo-words in order to determine the type of reading deficit (phonological or lexical) and to identify the way of reading used by the child (direct or indirect). The results resulted in the validity and reliability of the test for evaluating and classifying reading ability and dyslexia. The scale can also be used to diagnose cases of people with reading difficulties